Dichlorido(η6-p-cymene)[tris(2-cyanoethyl)phosphine]ruthenium(II) - Henderson, William; Nair, Ashwin Gopalan; Halcovitch, Nathan R.; Tiekink, Edward R. T. * (MDPI, 2018)
The tris(2-cyanoethyl)phosphine (tcep) complex [RuCl2{P(CH2CH2CN)3}(η 6 -p-cymene)] (p-cymene = p-CH3C6H4 iPr) was synthesised by the bridge-splitting reaction of the chlorido-dimer[RuCl2(η 6 -p-cymene)]2 with tcep. The complex was characterised by a single-crystal X-ray structure determination as well as NMR spectroscopy, ESI mass spectrometry, and microelemental analysis. X-ray crystallography shows the ruthenium atom is coordinated by p-cymene in a η 6 -fashion, two chlorides and the phosphorus atom of the tcep ligand with the donor set defining a distorted octahedral geometry. The ESI mass spectrometry study reveals that the complex readily forms negative ions [M + Cl]− and [2M + Cl]− by association with a chloride ion.